Application of Inquiry Learning Model Assisted Interactive Media on Material Shape and Energy Change to Improve Critical Thinking Skills of Elementary School Students - Afrida L Simanjuntak; Neni Hermita; Zetra Hainul Putra (STAI Hubbulwathan Duri, 2022)
An ability to think critically is to comprehend, apply, and analyse the truth of a given problem. There is a need for an efficient pedagogical framework that can help students develop critical thinking abilities while studying science. The goal of this research was to analyse the efficacy of an interactive media-assisted inquiry learning methodology applied to the topic of form and energy change in developing students' critical thinking skills. This study involved two fourth-grade classes at a Pekanbaru elementary school and took offline over two months (February and March 2022). There were 16 female and 9 male students in the experimental class and 14 female and 11 male students in the control class, respectively, who made up the research sample. In all, fifty students took part in the research. Information gleaned from before and after an experiment. The research approach is Quasi-experimental, utilising the Nonequivalent Control Group Design as the research shape. The t-test, a method for testing hypotheses, was used to assess the data. As can be seen from the data, the significance level for hypothesis testing was 0.032 (2-tailed). When this number is less than 0.05, H0 is rejected, and Ha is approved. Students' ability to think critically has improved as a result of using the media-assisted inquiry learning approach applied to the transformations of matter and energy, as shown by the results of this study.